AJARAN SUNAN BONANG TENTANG MUSYAHADAH - Muhammad Isa Anshory (MAMBA'UL 'ULUM, 2021)
Today the Ummah is experiencing a crisis in Islamic civilization. One indicator is the occurrence of spiritual degradation among them, even though the spiritual dimension of Islam has inspired the civilization as a whole. Therefore, efforts to revitalize Islam must start from a re-understanding of this matter. Wali Sanga is seen as the party who succeeded in building Islamic civilization in this country. Their teachings are widely accepted by Muslims today. Among the Wali Sanga teachings related to the spiritual dimension of Islam that is important to study is the teachings of Sunan Bonang about musyahadah. Musyâhadah is part of ihsân which is the highest level in Islam. Musyâhadah needs to be cultivated in the soul of Muslims in the midst of a civilization crisis, spiritual crisis, and crises in various dimensions of life. The purpose of this research is to describe how the teachings of Sunan Bonang about musyâhadah and to trace the extent of the influence of the thoughts of previous scholars on these teachings. The method used is literature study, which is how research works by searching for data through books and other written sources related to the problem. Based on this research, Sunan Bonang taught that a believer should always remember Allah in every situation so that he is able to concentrate his inner eye vision only on Allah. Everything other than Allah disappeared from his heart so that whatever could be seen by his eyes always reminded him of the Creator alone. Wherever he is, he feels with Allah (sortie Lan Pangēranê). This is what is meant by musyahadah. The teachings of Sunan Bonang about musyahadah were heavily influenced by previous scholars, such as Amru bin Uthman Al-Makki, Abu Sa'id Al-Kharraz, Abu Ali Ad-Daqqaq, and so on.